Airway Thiol-NO Adducts as Determinants of Exhaled NO - Pophal, Megan; Grimmett, Zachary W.; Chu, Clara; Margevicius, Seunghee; Raffay, Thomas; Ross, Kristie; Jafri, Anjum; Giddings, Olivia; Stamler, Jonathan S.; Gaston, Benjamin; Reynolds, James D. (Antioxidants, 2021)
Thiol-NO adducts such as S-nitrosoglutathione (GSNO) are endogenous bronchodilators in human airways. Decreased airway S-nitrosothiol concentrations are associated with asthma. Nitric oxide (NO), a breakdown product of GSNO, is measured in exhaled breath as a biomarker in asthma; an elevated fraction of expired NO (FENO) is associated with asthmatic airway inflammation. We hypothesized that FENO could reflect airway S-nitrosothiol concentrations. To test this hypothesis, we first studied the relationship between mixed expired NO and airway S-nitrosothiols in patients endotracheally intubated for respiratory failure. The inverse (Lineweaver-Burke type) relationship suggested that expired NO could reflect the rate of pulmonary S-nitrosothiol breakdown. We thus studied NO evolution from the lungs of mice (GSNO reductase −/−) unable reductively to catabolize GSNO. More NO was produced from GSNO in the −/− compared to wild type lungs. Finally, we formally tested the hypothesis that airway GSNO increases FENO using an inhalational challenge model in normal human subjects. FENO increased in all subjects tested, with a median t1/2 of 32.0 min. Taken together, these data demonstrate that FENO reports, at least in part, GSNO breakdown in the lungs. Unlike GSNO, NO is not present in the lungs in physiologically relevant concentrations. However, FENO following a GSNO challenge could be a non-invasive test for airway GSNO catabolism.